DAMPAK HUKUM KENAIKAN TARIF PUNGUTAN EKSPOR KELAPA SAWIT TERHADAP HILIRISASI INDUSTRI DAN KEPASTIAN HUKUM BAGI EKSPORTIR - Loso Judijanto (INTELIGENSIA MEDIA, 2026)
This study examines the legal implications of the increase in palm oil export levies on industrial downstreaming and legal certainty for exporters. The policy of increasing export levies is viewed as a state instrument to encourage the domestic processing of palm oil products in order to create greater added value, strengthen downstream industries, and support the national downstreaming agenda. However, dynamic changes to the tariff also give rise to legal consequences in the form of potential legal uncertainty for exporters, particularly in contract planning, cost calculations, and adjustments to trade strategies. This study employs a normative approach using a literature review method that examines legislation, academic literature, and official sources relating to palm oil export levy policy. The findings indicate that an increase in export levy rates has the potential to positively drive the downstream processing of the palm oil industry; however, its effectiveness is highly dependent on regulatory consistency, technical clarity in implementation, and the assurance of legal certainty for business operators. Therefore, export levy policies must be designed proportionately to ensure that industrialisation objectives and legal protection are balanced.